The Relationship between Stubbornness and Top Service ability in Student Volleyball Games - Yudi Ikhwani (Universitas Serambi Mekkah, 2021)
The purpose of this study was to determine the relationship between togok flexibility and top service ability in volleyball games at SMA Negeri 1 Lampeuneurut Aceh Besar students. This research is quantitative descriptive, that descript the relationship between two variables. The population in this study were students of SMA Negeri 1 Lampeuneurut Aceh Besar, amounting to 448 people. The sample in this study was taken by purposive sampling technique and obtained 25 students who got a minimum score of 8.5 in volleyball in sports subjects. The data collection techniques used in this study were: (1) togok flexibility was measured by bridge-up test (2) Upper serve ability was measured by volleyball service skill test. analysis of data obtained from the results of tests and measurements conducted on 25 samples, the data were processed and analyzed with statistics which aim to determine how big the relationship between variables. The results showed that there was a significant relationship between togok flexibility and the ability to serve in volleyball game.